High prevalence of Mycobacterium tuberculosis bacteraemia among a cohort of HIV-infected patients with severe sepsis in Lusaka, Zambia. (May 2017) - Muchemwa, Levy; Shabir, Lakhi; Andrews, Ben; Bwalya, Mwango
Tuberculosis is recognised as one of the leading causes of severe sepsis among HIV-infected patients. Most patients with Mycobacterium tuberculosis bacteraemia have advanced HIV disease with CD4 counts less than 100 cells/μl and its presentation is non-specific in most instances. This was a cross-sectional study which was done by analyzing data from 201 adult HIV-infected patients who met the inclusion criteria for severe sepsis. The prevalence of Mycobacterium tuberculosis bactraemia in the study population was 34.8%. Severe sepsis caused by other etiologies was observed in 33 (16.4%) of the participants. Concomitant infection of Mycobacterium tuberculosis bactraemia with other organisms is not uncommon in patients with severe sepsis. This cohort of HIV-infected patients had severe immunosuppression with a median CD4 count of 51 (20–136) cells/μl with moderate anaemia, mean haemoglobin 8.0 (3.0) g/dl, and were generally underweight with a mean mid upper arm circumference (MUAC) of 21.0 (3.4) cm. Mycobacterium tuberculosis bacteraemia is very common in HIV-infected patients with advanced HIV disease who present with severe sepsis. Mycobacterium tuberculosis bacteraemia co-infection with aerobic organisms is not uncommon. Factors that were independently associated with Mycobacterium tuberculosis bacteraemia in our study population were MUAC and sodium level.